The Relationship Between Facilities, Tourist Attractions and The Interest of Tourists to Revisit Lake Aur - Aulia Berliana; Esya Alhadi; Rini (Takaza Innovatix Labs Ltd., 2026)
Tourism plays a vital role in regional economic growth and cultural preservation, yet Lake Aur in Musi Rawas Regency struggles to sustain repeat visits despite its promising natural potential. This study examines the relationship between tourist facilities (X1), attractions (X2), and tourists' interest in revisiting Lake Aur using a descriptive quantitative approach. Data from 100 repeat visitors (minimum 2 visits) were collected via Likert-scale questionnaires from a 2024 population of 48,478 tourists, analyzed through multiple linear regression in SPSS 26 following validity, reliability, and classical assumption tests. Results reveal that both facilities and attractions positively and significantly influence revisit interest, both partially and simultaneously, accounting for 38.9% of the variance. The study recommends enhancing infrastructure and unique attractions like eco-trails to boost loyalty, with future SEM models addressing sample limitations